Q Quality Red Spinach Ice Cream With Albedo Peel Extract Paste Stabilizer - Franciscus Sinung Pranata (Pro Food, 2022)
Ice cream is a semi-solid dairy product and is consumed as a snack or dessert. This study used natural ingredients in the form of red spinach as a natural dye because of the anthocyanin content and albedo of pomelo peel as a source of pectin. This study was conducted to determine the physical, chemical and microbiological quality of ice cream with the addition of red spinach extract and pomelo peel albedo extract paste, to determine the best concentration of red spinach extract to produce ice cream containing antioxidants and to determine the effect of adding orange peel albedo extract paste. Bali as a stabilizer for the quality of red spinach extract ice cream. This study was conducted using a completely randomized design (CRD) with four comparisons of red spinach extract and pomelo peel albedo extract, namely 0:0 (K), 4:0,5 (A), 6:1 (B), and 8:1,5 (C). The results of the research on ice cream products obtained overrun 71.67-100%, melting rate 883-1024 seconds, fat content 8.72-12.80%, protein content 4.40-9.31%, total solids 23.75-26.67%, total sugar 20.73-21.67% and antioxidant content 2.98-75.07%. The results of the total plate number based on the study were 2.00-6.60 CFU/mL and the presence of Salmonella in all treatments was negative. The best quality ice cream in this study was ice cream treatment C with the addition of red spinach extract and albedo paste extract of pomelo peel at 8:1.5%, based on the results of physical, chemical and microbiological tests with the best results.